Increasing Male Participation in Family Planning Through Reproductive Health Education - Muhamad Amir (Journal of Public Health Indonesian, 2025)
Male participation in family planning remains low globally due to traditional gender norms, misconceptions about contraception, limited male friendly health services, and insufficient reproductive health education. This article examines how reproductive health education can enhance male involvement using a Systematic Literature Review guided by PRISMA 2020. From an initial pool of 1,024 studies, 83 met the inclusion criteria and were thematically synthesized. Findings indicate that reproductive health education increases men’s knowledge, improves couple communication, reduces myths about contraceptive methods, and enhances acceptance of both male and female contraceptives. Community based interventions, gender transformative education, and digital learning approaches demonstrated the strongest impact, particularly when integrated with supportive health systems and inclusive policies. The study underscores that strengthening male participation in family planning requires multi dimensional strategies involving health system reforms, community engagement, and comprehensive reproductive education to ensure sustainable program outcomes